2007
DOI: 10.1111/j.1440-1584.2007.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychological distress, anxiety and depression in rural communities in Australia

Abstract: A third of the rural population reported psychological distress, with the highest prevalence observed in middle-aged men and women. Thus, health professionals should attend not only to physical health, but also to mental health status in this age group. It is also important to target prevention strategies at the 20% who reported moderate levels of psychological distress in order to prevent the development of more serious conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
91
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 20 publications
15
91
3
3
Order By: Relevance
“…Yet this gender difference is not universal. For instance, no gender difference was observed in Mexican Americans (Aranda et al 2001), in African, Asian, Central American and South American immigrants in Norway (Thapa and Hauff 2005), in rural Australians (Kilkkinen et al 2007) and in older Chinese (Chou 2007). The widespread gender difference points to three alternative hypotheses.…”
Section: Prevalence Of Psychological Distressmentioning
confidence: 96%
“…Yet this gender difference is not universal. For instance, no gender difference was observed in Mexican Americans (Aranda et al 2001), in African, Asian, Central American and South American immigrants in Norway (Thapa and Hauff 2005), in rural Australians (Kilkkinen et al 2007) and in older Chinese (Chou 2007). The widespread gender difference points to three alternative hypotheses.…”
Section: Prevalence Of Psychological Distressmentioning
confidence: 96%
“…A priori, we hypothesised that scores would differ by gender and age [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]; this was confirmed in the initial analysis, and thus, results are presented for females and males separately, and within gender, by 5-year age group.…”
Section: Anxiety and Depression Scoresmentioning
confidence: 99%
“…data collected from a representative sample of the general population against which all subsequently collected data can be compared) have remained limited. Our recent review of the literature identified only 20 papers that could be described as reporting normative data from the HADS [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The studies were conducted mainly in Europe, included sample sizes ranging from 94 [17] to 62,344 [13] participants and were sourced using a variety of different techniques, for example all residents in a particular region/country [13,17,19], a stratified random sample of three age cohorts [12,20] and adults registered with a particular Primary Care practice [8,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depression with HADS-D is similar to other epidemiological studies in the region. 15,16 Gold standards such as the Structured Clinical Interview for DSM-IV 17 were beyond the scope of the study but could probably have further clarified which measure performed better for screening. The sample was selected because of type 2 diabetes status.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%